2014
DOI: 10.1111/jvp.12144
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of oral chlortetracycline in nonpregnant adult ewes

Abstract: The objectives of this study were to determine plasma concentrations and pharmacokinetic parameters of feed-grade chlortetracycline (CTC) in sheep after oral administration of 80 or 500 mg/head daily, divided into two equal doses given at 12-h intervals for 8 days. These are the approved, and commonly used but unapproved, feed additive doses, respectively, in the United States for the prevention of ovine infectious abortion. Blood samples were collected just prior to dosing at 0, 12, 24, 72, 96, and 192 h, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…A report of tetracycline in rats demonstrated similar concentrations in fetal and maternal plasma once steady‐state had been reached (Olanoff & Anderson, ). Mean maternal plasma concentrations were consistent with our previous study in nonpregnant ewes (Washburn et al., ). For example, the mean concentration of CTC on Day 7 (Hour 168) of treatment was 109 ± 28 ng/ml, whereas in the previous study, the mean concentration at the same time was 81 ± 30 ng/ml.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…A report of tetracycline in rats demonstrated similar concentrations in fetal and maternal plasma once steady‐state had been reached (Olanoff & Anderson, ). Mean maternal plasma concentrations were consistent with our previous study in nonpregnant ewes (Washburn et al., ). For example, the mean concentration of CTC on Day 7 (Hour 168) of treatment was 109 ± 28 ng/ml, whereas in the previous study, the mean concentration at the same time was 81 ± 30 ng/ml.…”
Section: Discussionsupporting
confidence: 91%
“…It has been suggested that the feeding of an extra‐label dose of CTC of up to 500 mg/head/day may result in increased efficacy of managing sheep flocks in the last trimester to prevent abortion outbreaks from campylobacteriosis (Menzies, ). However, a recent study by the current investigators (Washburn et al., ) found that plasma levels of nonpregnant sheep fed the unapproved dose of 500 mg/head/day were far below the minimum inhibitory concentrations (MIC) of tetracyclines reported in the literature for most Campylobacter jejuni isolates collected from livestock and isolates associated with abortion outbreaks (Oporto, Juste, & Hurtado, ; Sahin et al., ; Scott et al., ). Further, the extra‐label use of this elevated level of CTC is an illegal usage of a feed additive in the US.…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…Reports of resistance and lack of efficacy have prompted investigation of the pharmacokinetics of the common feed‐additive chlortetracycline. Feeding chlortetracycline to sheep at the approved dose and at the higher, unapproved dose results in subtherapeutic levels in pregnant ewe plasma and mostly undetectable levels in fetal tissues and amniotic fluid (Washburn et al., , ). Chlortetracycline in feed requires a veterinary feed directive, and extra‐label use or use of increased doses of feed additives is illegal in the United States.…”
Section: Introductionmentioning
confidence: 99%